1980
DOI: 10.1575/1912/2206
|View full text |Cite
|
Sign up to set email alerts
|

The marine geochemistry of thorium and protactinium

Abstract: Suspended particulate matter was collected by sediment traps deployed in the Sargasso Sea (Site 82), the north equatorial Atlantic (Site E), the north equatorial Pacific (Site p), and the Panama Basin (STIE Site). Additional samples of suspended particles were obtained by in situ filtration at Site F., at the STIE Site, and in the GuatemalaBasin. Concentrations of dissolved Tn and Pa were determined by extraction onto manganese dioxide adsorbers at Site P, at a second site in the Sargasso Sea (Site D), at the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

1982
1982
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 21 publications
(30 reference statements)
0
5
0
Order By: Relevance
“…Because of its particle affinity, virtually all of the 231 Pa produced in the open ocean water column is scavenged onto particles and accumulates in sediments (Anderson et al, 1983a). Actinium-227 is more soluble than its parent (Nozaki, 1993;Anderson, 1980), thus 227 Ac produced through the decay of sediment-bound 231 Pa is released to the overlying water column.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of its particle affinity, virtually all of the 231 Pa produced in the open ocean water column is scavenged onto particles and accumulates in sediments (Anderson et al, 1983a). Actinium-227 is more soluble than its parent (Nozaki, 1993;Anderson, 1980), thus 227 Ac produced through the decay of sediment-bound 231 Pa is released to the overlying water column.…”
Section: Introductionmentioning
confidence: 99%
“…Work by Sakamoto et al (2002) suggests that Ac also has an affinity for Fe oxyhydroxides. Although the few existing measurements of particulate 227 Ac in the open ocean suggest that it is not particle reactive (Anderson, 1980;Geibert et al, 2002), Moore (1992) suggests that 227 Ac may be more particle reactive than Ra in particle-rich environments. In this study we examine the activities of both dissolved and particulate 227 Ac in a hydrothermal plume emanating from the high temperature TAG hydrothermal vent.…”
Section: Introductionmentioning
confidence: 99%
“…The sources of data for particle fluxes (s), residence times of Th (TP), and mean depth (h in m) are given in Table 2. Li et al 1980Li et al 1980Knauss et al 1978Brewer et al 1980Brewer et al 1980Li et al 1980Anderson 198 1 Moore et al 198 1 Minagawa and Tsunogai 1980Minagawa and Tsunogai 1980Minagawa and Tsunogai 19 80 Santschi et al 1980Santschi et al 1980Santschi et al 1980Li et al 1979, 1981Anderson et al 1983Anderson et al 1983 (Krishnaswami et al 1976;Brewer et al 1980;Li et al 1980 comes from observations (Neihof and Loeb 1972;Hunter and Liss 1979;Lion et al 1982) that natural particles are coated with organic or Fe-Mn-hydroxide films which give them relatively uniform outer surfaces for adsorbing trace metals.…”
Section: Notesmentioning
confidence: 99%
“…During the preparation of this paper we became •aware of recen t measurements by Moore [1981] Because of the large volumes of seawater that must be processed for analysis of 23øTh and 228Th, we adopted a scheme for sampling in situ. Submersible, battery-powered, pumping systems, initially described by Sp•;ncer and Sachs [1970•;and later modified during the GEOSECS program [Krishnaswami' et al, 1976b], were used to force the water first through a coarse prefilter (62-/am mesh Nitex), then through fi fine membrane filter' (1.0-/am NuclePore, preweighed), then th,rough a cartridge packed with, Nitex netting that was Coal•ed with manganese dioxide to scavenge the dissolved Th isotopes [Anderson, !981], and fina!ly through a flow meter to record the volume of water that was Complete details of our analytical methods are given by Anderson [ 1981] Table 2. The particulate Th results are based on the 1-62-tam fraction that was caught by the Nuclepore filters.…”
Section: Introductionmentioning
confidence: 99%
“…It will be argued in the following section that the tendency of the Th isotopes to be partitioned differently between dissolved and particulate forms is related to the differences in radioactive half-life and to the kinetics of the scavenging process. Measurements of U (not listed in Table 2 but given by Anderson [1981]) showed that negligible amounts of the 234Th and 23øTh in the particulate matter are supported by decay of the parent radionuclides. We assume this to be the case also for 228Th.…”
Section: Introductionmentioning
confidence: 99%